PEMANFAATAN DAN PENATAAN RUANG PUBLIK TEPI PANTAI ULEE LHEUE KOTA BANDA ACEH - Roni O. Saragih; Izziah Izziah; Muhammad Isya (Prodi Magister Teknik Sipil Unsyiah, 2018)
One of the growing areas of Banda Aceh city as a public space is the coast of the Ulee Lheue beach. This corresponds with the Spatial Plan of Banda Aceh city in 2009-2029 clauses 58, which are: wheres explained that development of tourists area and public spaces directed to the former area of normalization of Krueng Aceh (Pante Riek and Lambhuk) and Ulee Lheue. This research aims to review the utilization of Ulee Lheue coast as public space and the optimization of the arrangement. The research method used is a descriptive method with mixed method approach. Data collections are done by observation, questionnaire, and interview. A sample selected with random sampling technique based on Slovin equation. Questionnaire uses a Likert scale. Validity and reliability test are used Microsoft Excel. Then conduct SWOT analysis. The results of the research show that Coastal of Ulee Lheu beach has a strategic role in shaping the face of tourism city of Banda Aceh city but still not managed optimally. Improvement of Ulee Lheue coastal function can be done by rearranging the physical area and its management by complete supporting facilities and infrastructure and also disciplinary maintenance so in accordance with its designation as tourism area and public space.